Virtual-learning Content Management System for Problem-Based Learning (PBL) courses - Abu Kasim, Norul Ashikin; Gunawan, Teddy Surya (2012)
This paper presents the design of Virtual-Learning Content Management System to be used by students and instructors a like using problem-based learning (PBL) as the instructional methodology. V-LCMS is designed and implemented at Mara Professional College Indera Mahkota (MPCIM). It details the rationale for implementing V-LCMS as well as reporting the intended learning outcomes by assessing the students' achievements. The achievement is reported as a case study conducted in an undergraduate level course. The students participated in this V-LCMS case study tests are correlated with their achievement of the course's learning objectives. The paper focuses on the uploading of the notes and assessments easily and quickly, and also easing the interactions between the instructors and the students. In addition, the system also aims to develop a web site using Interactive and Incremental Development (IDD) prototype. To develop this system, the software chosen is Joomla 1.5, Windows XP as an operating system, PHP 5.2.5 as a programming language, MySQL 5.0 as a database and Apache 2.2.8 as a web server. Other advantage of this V-LCMS is it makes it easier for the students to interact with instructors using forum or chat room. The PBL was implemented using the interaction between students and lecturers using both facilities, i.e. forum and chat room. Overall, not only the system facilitates the instructors, but also it facilitates their students in terms of receiving the knowledge imparted.